Mammographic Doses Measurement for A Thick Compressed Breast and the Relationship Between Them - Sharif, N. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was done in Baghdad teaching Hospital by using developed instrument type GIOHO and included a number of patients with compressed breast thickness (7,8,9,10)cm . The relationship between radiation dose and breast thickness was linear. All results were compared with the international standered values that measured by the International Nuctear Agency and Europeon sources ,it was found that it is in consistance or has a little difference . The study showed that the mean absorbed dose may be determined by using TLD measurement below 10 mGy and the glandular dose was (1.45 mGy) and this can not be measured directly but it is calculated under certain assumption from the experimentlly determined entrance surface dose(ESDpa) by the use of the so-called conversion factores and compare the exposure conditions to those given in the European quality criteria document.